A INFLUÊNCIA DA INTERNAÇÃO SOBRE PACIENTES TABAGISTAS: UMA REVISÃO DE LITERATURA - Alice Leite Mesquita; Clara Braga dos Santos Azevedo; Dennys Ivanovas Beltrão; Guilherme Leite Mesquita; Vanessa Vieira Bastos; Marcelo Fouad Rabahi; Lídia Acyole de Souza Oliveira (UniEVANGÉLICA, 2015)
Objective: To describe the epidemiology of smoking in hospitals, to understand the approach for hospitalized smoking patients, comparing the patient's motivational stage before and during hospitalization as well as interventions during the hospitalization period and after discharge. Methods: This is an integrative literaturereview. The articles search strategy includes research in online databases: SciELO, PubMed, Virtual Health Library and BIREME, using the MeSH: "hospitalization", "smoking", "smoking cessation." Inclusion criteria were articles published in English and Portuguese, full access availability to the articles and publication period varying from 2005 and 2015. Results: The levels found in smoking prevalence range from 12.1 to 18.7%. After the hospitalization, the most found motivation stage was the active stage (34.1%). The evolution of the motivational stage is the main evidence that hospitalization interferes positively in smoking cessation. However the patient may suffer from nicotine withdrawal syndrome, which requires specific care for the effectiveness of promoting the cessation of smoking. This effectiveness depends on the following given to the addiction treatment of post-discharge inpatients. Conclusion: It is suggestive that hospitalization increases the ease of approach towards smoking cessation and towards the success of smoking cessation, certainly, duel to the motivacional stage advances, though it is not common to find protocols for the treatment of smoking patients focused at the abandonment of smoking